PRA-RANCANGAN INDUSTRI PENYULINGAN AKAR WANGI (VETIVERIA ZIZAINOIDES (L.) NASH) DENGAN PERLAKUAN AWAL PENCUCIAN : PENGARUH PERLAKUAN AWAL PERAJANGAN DAN PENYIMPANAN AKAR WANGI (VETIVERIA ZIZAINOIDES (L.) NASH.) TERHADAP PEROLEHAN MINYAK AKAR WANGI DENGAN METODE WATER AND STEAM DISTILLATION - Sephia, Chaerunisa
Vetiver root oil is one of Indonesia’s leading export commodities. The center production of vetiver root oil in Indonesia is Garut, West Java. Some problems faced by vetiver root oil producers in Garut is lacking in the yield and the quality of vetiver root oil. The most common distillation method used by the community is water and steam distillation. This study aims to determine the effect of chopping treatment and storage of raw materials on the yield of vetiver root oil. The variables observed in this study are water content, drying rate during the storage, oil recovery (oil yield based on wet and dry basis, refining speed, and forecasting the end of refining time). Data analysis used RAL with ANOVA test at ? = 0,05, Ftest and Durbin Watson test. Based on the results of the study, chopping treatment and storage of raw materials affects the vetiver root oil yield. The highest yield of vetiver root oil is in the treatment of two weeks storage without chopping of 0.56% yield on a dry basis and 0.45% on a wet basis. The highest refining rate of all treatments was two weeks storage without chopping which is 0.076%/hour. Forecasting results show the end of the fastest distillation time with the highest final volume is two weeks storage without chopping treatment with an estimated distillation time of 10 hours 30 minutes and a final volume of 7 mL of 2 kg raw material. Based on the variables of dry basis yield, wet basis yield, distillation speed, storage of vetiver root for two weeks without chopping can be used as one solution to increase the vetiver root oil.